Time to adjuvant chemotherapy and overall survival in advanced-stage ovarian cancer patients in England: a population-based retrospective cohort study - L. Steventon; S. Nicum; K. Man; D. Dodwell; Z. Wang; A. Patel; B. Pickwell-Smith; L. Wei; P. Chambers (ESMO Real World Data and Digital Oncology)
Background and purpose: In advanced ovarian cancer, delayed time to chemotherapy (TTC) has been associated with poorer survival outcomes; evidence is conflicting, however. This study investigated the impact of patient demographic factors on TTC and assessed whether TTC was associated with 5-year overall survival. Materials and methods: A retrospective cohort study was conducted using English national data for women with advanced-stage ovarian cancer (IIB-IV), treated with primary debulking surgery (PDS) or interval debulking surgery (IDS) + adjuvant carboplatin/paclitaxel chemotherapy between 1 January 2014 and 31 December 2019. Cox proportional hazards regression was used to compare the primary outcome of 5-year overall survival between patients treated within ≤6 weeks (0-42 days) or >6 weeks (>42 days) of surgery. Results: A total of 4619 patients were included. Of these, 42% (n = 1940) received PDS and 58% (n = 2679) IDS. Median TTC was 45 days [interquartile range (IQR) 37-55 days] for PDS and 34 days (IQR 27-42 days) for IDS. TTC ≤6 weeks was associated with 5-year survival in the IDS cohort (HR 1.18, 95% CI 1.06-1.33, P = 0.003), but not in the PDS cohort (HR 1.04, 95% CI 0.90-1.21, P = 0.6). A higher proportion of patients from the most socioeconomically deprived backgrounds waited >6 weeks (45%, n = 291) compared with the least deprived (37%, n = 398). Adjuvant chemotherapy was initiated in 72% of patients in London within ≤6 weeks compared with 47% in the North West. Conclusions: Median TTC exceeded 4-week guidance from the European Society of Medical Oncology. TTC >6 weeks was associated with reduced 5-year survival in patients treated with interval surgery, but not primary surgery. Regional disparities in TTC were observed.